2013
DOI: 10.1111/pedi.12056
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial spread of enterovirus infections at the clinical onset of type 1 diabetes

Abstract: BACKGROUND: At the clinical onset of type 1 diabetes mellitus (T1D), enterovirus \ud (EV) infections are suspected to play a role. EVs in blood are seen as a possible\ud biomarker of T1D. EV infections may occur in temporal and geographic clusters and\ud may spread within families. OBJECTIVE: We checked whether EVs were present in the\ud blood of newly diagnosed diabetic probands and of their consenting siblings and\ud parents. We aimed at evaluating the frequency of EV infection, whether infections\ud were sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 45 publications
(65 reference statements)
3
35
0
Order By: Relevance
“…Is this observation indicative of an inefficiently resolved infection in these individuals, which might have spread to the pancreas? If so, it would be consistent with emerging data showing that low-level, persistent enteroviral infections can be detected in the peripheral blood of other recently diagnosed patients (8). Importantly, when IFN signature and low-level infection are considered together with evidence that a low-level, noncytolytic, persistent enteroviral infection of b-cells occurs in pancreata from cohorts in Italy (9), the U.K. (10,11), and the U.S. (network of pancreatic organ donors, nPOD) (11), one can envision a scenario where a primary acute viral infection leads to a secondary long-term persistent pancreatic infection that could ultimately drive the development of disease.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Is this observation indicative of an inefficiently resolved infection in these individuals, which might have spread to the pancreas? If so, it would be consistent with emerging data showing that low-level, persistent enteroviral infections can be detected in the peripheral blood of other recently diagnosed patients (8). Importantly, when IFN signature and low-level infection are considered together with evidence that a low-level, noncytolytic, persistent enteroviral infection of b-cells occurs in pancreata from cohorts in Italy (9), the U.K. (10,11), and the U.S. (network of pancreatic organ donors, nPOD) (11), one can envision a scenario where a primary acute viral infection leads to a secondary long-term persistent pancreatic infection that could ultimately drive the development of disease.…”
supporting
confidence: 73%
“…However, individuals with susceptibility to T1D have genetic variants that include key signaling (4), which will present b-cell and viral antigens to the infiltrating immune cells (5). Following the recognition of their respective antigens, activation of immune cells in an environment lacking in normal regulatory control (6) will lead to both the expansion of effector cells (7) and maturation of B cells that can produce b-cell-specific antibodies and viral-specific antibodies (8). These are frequently detected together in individuals exhibiting diabetes-associated autoimmunity.…”
mentioning
confidence: 99%
“…Gamble et al were the first to report a possible link between EV infection and type 1 diabetes in 1969 [11,12]. Evidence for the contribution of Coxsackievirus B infections in the pathogenesis of type 1 diabetes abounds [13][14][15], yet several other EVs species, including Coxsackievirus A [16][17][18], echoviruses [16,17] and EVs of A-D species [19], may also have a role. Cases of new-onset type 1 diabetes occur in seasonal patterns [11,20], sometimes in clusters or small outbreaks, often peaking 1-2 months after high EV infection activity [21].…”
Section: Introductionmentioning
confidence: 99%
“…Cases of new-onset type 1 diabetes occur in seasonal patterns [11,20], sometimes in clusters or small outbreaks, often peaking 1-2 months after high EV infection activity [21]. A recent study on intrafamilial spread of EV infections reported that 20% of siblings of diabetic probands acquired type 1 diabetes with a latency of 3-25 months [19]. Evidence for this association is supported by detection of EVs in the blood [13,14,17,22], pancreas [15,[23][24][25][26] and gut mucosa [27] of patients with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…These can cause severe respiratory illness and a range of neurological diseases, from aseptic meningitis to encephalitis and paralysis(Kreuter et al, 2011; Pallansch et al, 2013; Tao et al, 2014). Infections with other EV, such as CVB3, may contribute to diabetes (Salvatoni et al, 2013; Yeung et al, 2011) and heart disease(Chapman and Kim, 2008; Cooper, 2009). …”
mentioning
confidence: 99%